2019
DOI: 10.1002/ehf2.12419
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning‐based prediction of heart failure readmission or death: implications of choosing the right model and the right metrics

Abstract: Aims Machine learning (ML) is widely believed to be able to learn complex hidden interactions from the data and has the potential in predicting events such as heart failure (HF) readmission and death. Recent studies have revealed conflicting results likely due to failure to take into account the class imbalance problem commonly seen with medical data. We developed a new ML approach to predict 30 day HF readmission or death and compared the performance of this model with other commonly used predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 23 publications
3
80
0
1
Order By: Relevance
“…The HF population in China differs from that in Western countries, including notably more stroke and a lower BMI, 1,9,22 making data derived from Western populations likely to be not applicable. In addition, previously published studies on HF readmission or death risk model have mainly depended on cardiac conditions, 5,6,23 whereas they have focused less on the impact of noncardiac factors such as stroke and anaemia, which were the major factors for all‐cause readmission or death in elderly patients with HF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HF population in China differs from that in Western countries, including notably more stroke and a lower BMI, 1,9,22 making data derived from Western populations likely to be not applicable. In addition, previously published studies on HF readmission or death risk model have mainly depended on cardiac conditions, 5,6,23 whereas they have focused less on the impact of noncardiac factors such as stroke and anaemia, which were the major factors for all‐cause readmission or death in elderly patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…As many of readmissions and deaths are possibly predictable and preventable, 3,4 an easy‐to‐use and accurate model to predict the risk of all‐cause readmission or death has been noted 5–7 . However, it is suboptimal using a one‐size‐fits‐all approach to predict the risk of readmission or death for all patients with HF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 An abundance of studies has described the application of AI-based techniques to predict hospital readmission. [18][19][20][21][22][23][24][25][26] Although many studies have concluded that AI-based models are superior to traditional models for risk stratification, other studies have observed otherwise. 14,[27][28][29][30][31][32][33][34][35][36][37][38][39] While clinical factors have primarily been used to predict readmission, there has also been interest in incorporating sociodemographic factors into models to more accurately account for patients' sociopersonal contexts, which are increasingly recognized to affect health-related outcomes.…”
Section: Predictive Analytics For Hospital Readmissionmentioning
confidence: 99%
“…Previous studies have modeled risk of hospitalization, long-term survival rates, and mode of death prediction as a result of heart failure [ 16 - 18 ]. Models used features related to clinical status, therapy, and laboratory parameters including home-based physiological telemonitoring [ 19 ].…”
Section: Introductionmentioning
confidence: 99%